A SEMANTIC ANALYSIS OF QURANIC KINSHIP TERMS AND ITS RELEVANCE TO DAILY CONVERSATIONAL USAGE - Dr. Ghulam Ahmad; Dr. Muhammad Sarwar; Dr. Khuda Bakhsh; Dr. Makkiah Nabi Bakhsh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
This review paper delves into the significance of Quranic kinship terms in teaching the Arabic language, highlighting their role in fostering cultural understanding and communication skills. It explores the advantages and strategies of incorporating these terms into language instruction and assesses learners’ perceptions of their utility. Using a mixed-methods approach, the study measures the impact of Quranic kinship term instruction on Arabic language skills. The article also provides practical techniques for learning a language through the usage of relatives’ terms, enhancing conversational proficiency and cultural competence.